Management of coarctation of the aorta in the first six weeks of life. Issue 4 (July 1970) - Meredith, G.; Sawyer, R.; Braimbridge, M. V.
Abstract : The position of surgery in the management of coarctation of the aorta in infants under 6 weeks of age is still not established, primarily because of the high mortality associated with resection of the coarctation. Five patients with coarctation in this age group who have undergone resection at St. Thomas' Hospital are described. One patient died at operation and one other has required a second operation to relieve restenosis of the anastomosis. The advisability of banding the pulmonary artery at the time of resection of coarctation complicated by other left-to-right shunts is suggested.